Students' Physical Fitness Profile Reviewed From The Perspective Of Sports Physiology - Jumaidi Jumaidi; Tri Bayu Norito; Ilham Ilham; Wawan Junresti Daya; Boy Indrayana (S&Co Publishing, 2026)
Physical fitness at school age is important to describe students' physiological readiness for activities, learning, and carrying out daily activities. This study aims to describe the physical fitness profile of students at SMAN 5 Jambi City based on the perspective of exercise physiology and to compare profile trends by gender. The study used a descriptive quantitative approach with a cross-sectional design. Secondary data were obtained from measurements of body mass index (BMI), V Sit and Reach flexibility, 60-second Sit Up, 30-second Squat Thrust , and cardiorespiratory endurance using the PACER Test . The sample consisted of 20 students, namely 13 females and 7 males. Analysis was conducted descriptively using the mean, standard deviation, range, and distribution of categories. The results showed that most students had good nutritional status, good flexibility, adequate abdominal muscle endurance, and very good dynamic movement abilities. However, cardiorespiratory endurance was still low, with the largest proportion in the very low and low categories. In conclusion, students' flexibility and dynamic movement were classified as good, but cardiorespiratory endurance needs to be a priority for physical learning interventions